I’m gonna spawn - Virtanen, Inkeri (Taideyliopiston Kuvataideakatemia, 2024)
The master’s thesis project consists of an artistic and a literary part. The artistic component was exhibited at Kuva/Tila gallery during the Kuvan Kevät 2024 exhibition in 4.5.–2.6.2024, and featured five framed oil paintings. My thesis project addresses questions that emerged when I transitioned from a bachelor’s in textiles to a master’s in painting. This shift in perspective prompted me to critically examine my relationship with painting, not just as a medium but also as a larger framework. By comparing my thought processes while painting versus weaving, I began to uncover a larger theme centred on the concept of creation. The contrast between the painter’s visible role and the weaver’s often hidden labour raised questions about whose stories are highlighted and whose are erased. I explore these questions through figures like the earthworm, spider, and Yorkshire terrier, which serve as guides for thinking beyond human-centred narratives. They show how creation is not limited to the human, but shared across species —frog’s eggs in gelatinous sacs and the tarantula’s silk webs are not only acts of survival, but also acts of creation. In the written part of my thesis, I explore how materials themselves carry stories. By examining my own artistic practice, I aim to contextualise my work and reflect on my position as an artist, all while grappling with the violent history embedded in European painting. I reflect on my motives for painting and explain some of the thoughts behind the works created for this thesis project. Maintaining a dialogue with the processes and ways of thinking I learned while focusing more on weaving, I consider how to bridge the gap between these two distinct approaches. Coming to the conclusion that what seems to be crucial is an awareness and relationship to the materials. Recognising them as active participants in my work.
Keywords: maalaustaide; kuvataide; opinnäytteet; fi=maalaustaide|sv=måleri|en=Painting|